Density functional theory study of nitrogen-14 nuclear quadrupole coupling parameters of L-histidine hydrogen-bonded system - Elmi, Maryam Mitra (Magnetic resonance in chemistry : MRC, 2012)
Copyright © 2012 John Wiley & Sons, Ltd.